2001
DOI: 10.1086/323473
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the 3β-Hydroxysterol Δ24-Reductase Gene Cause Desmosterolosis, an Autosomal Recessive Disorder of Cholesterol Biosynthesis

Abstract: Desmosterolosis is a rare autosomal recessive disorder characterized by multiple congenital anomalies. Patients with desmosterolosis have elevated levels of the cholesterol precursor desmosterol, in plasma, tissue, and cultured cells; this abnormality suggests a deficiency of the enzyme 3beta-hydroxysterol Delta24-reductase (DHCR24), which, in cholesterol biosynthesis, catalyzes the reduction of the Delta24 double bond of sterol intermediates. We identified the human DHCR24 cDNA, by the similarity between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
263
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(271 citation statements)
references
References 46 publications
7
263
1
Order By: Relevance
“…The Seladin-1 gene (also named KIAA0018 and DHCR24, 24-dehydrocholesterol reductase) contains 9 exons spanning approximately 46 Kb of genomic DNA on chromosome 1p33-p31.1. [37][38][39] Previous data from our group identified Seladin-1 gene transcripts in ER Ϫ /PR Ϫ primary breast tumors using differential display reverse transcriptase (DDRT)-PCR. 40 In the present study, we have also observed that advanced-stage breast tumors (stages III and IV) showed higher levels of Seladin-1 gene expression compared to early-stage breast tumors (stages I and II), possibly reflecting its association with a more aggressive nature.…”
Section: Resultsmentioning
confidence: 99%
“…The Seladin-1 gene (also named KIAA0018 and DHCR24, 24-dehydrocholesterol reductase) contains 9 exons spanning approximately 46 Kb of genomic DNA on chromosome 1p33-p31.1. [37][38][39] Previous data from our group identified Seladin-1 gene transcripts in ER Ϫ /PR Ϫ primary breast tumors using differential display reverse transcriptase (DDRT)-PCR. 40 In the present study, we have also observed that advanced-stage breast tumors (stages III and IV) showed higher levels of Seladin-1 gene expression compared to early-stage breast tumors (stages I and II), possibly reflecting its association with a more aggressive nature.…”
Section: Resultsmentioning
confidence: 99%
“…To date, only two clinical cases of this biochemical disorder have been described. Although DHCR24 mutations of both alleles were demonstrated in both cases, 1 the clinical phenotypes of the two cases are very different. Through linkage analysis and biochemical studies of four individuals of a consanguineous Bedouin Israeli kindred, we now demonstrate a consistent phenotype of this rare human disorder.…”
Section: Introductionmentioning
confidence: 81%
“…To date, only two clinical cases of desmosterolosis (MIM 602398) have been described, and DHCR24 mutations of both alleles were demonstrated in both cases. 1 The phenotypes of the two cases are very 17 is of a boy (born at term) with microcephaly, agenesis of the corpus callosum, downslanting palpebral fissures, bilateral epicanthal folds, submucous cleft palate, micrognathia, mild contractures of the hands, bilateral clubfeet, cutis aplasia and persistent patent ductus arteriosus. At 40 months of age, he was severely developmentally delayed and had failure to thrive.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we found no similarities in the sterol pattern observed with HCV G3 to the metabolite patterns seen with enzyme dysfunction in well-characterized hereditary sterol disorders, such as 3b-hydroxysterol D 7 -reductase (Smith-Lemli-Opitz syndrome and desmosterolosis), 3b-hydroxysterol D 24 -reductase (desmosterolosis), 3b-hydroxysteroid-D 5 -desaturase (lathosterolosis), and 3b-hydroxysteroid-D 8 D 7 -isomerase (X-Linked Dominant Conradi-Hünermann syndrome; CDPX2). 21,30 Eradication of HCV G3 resulted in increased distal metabolite levels but no change in the lanosterol level, further suggesting that viral perturbation of the sterol pathway may occur at a point(s) distal from lanosterol and proximal to 7-DHC/cholesterol. Similar results were obtained when the changes before and after treatment metabolites were compared between SVR and non-SVR patients, and only postlanosterol metabolite changes differed with viral eradication.…”
Section: Discussionmentioning
confidence: 99%